Utilization of antenatal care services in a selected rural area in Bangladesh (Northern International Medical College Journal, 2015)
Background : Antenatal care, the care that a woman receives during pregnancy, helps to ensure healthy outcomes for mother and newborns. Utilization of antenatal care services is the basic component of maternal care on which the life of mothers and babies depend.Objectives : To find out the utilization of antenatal care services in a selected rural area in Bangladesh.Methodology : Descriptive cross-sectional study was conducted between January to June 2014 A total 199 married women of reproductive age who had a live baby below 5years of age, were selected purposively from village Islampur in Dhamrai Upzilla under Dhaka district. Data were collected by face to face interview using a pre-tested structured questionnaire.Result : The study revealed that 94.97% utilized ANC services among them 44.72% visited for ANC more than 4 times, 20.10% for 4 times and 30.15% less than 4 times during pregnancy. Health care centre was within walking distance. Most of them were young women aged between 23-27 years (45.72%) and 18-22 years (36.18%). Majority (33.16%) was educated up to secondary level but 83.42% were house wife. Economic status was lower economic group. Half of the respondents (52%) took ANC on their own and permission of husband and 95.97% received special care from their family during pregnancy. For birth planning 86.83% planned health provider to conduct delivery and 71.36% wanted hospital delivery. Majority (97.98%) took birth preparedness during pregnancy and 55% received antenatal care from qualified doctor. About 87% found them available on duty and good behavior was found by 70.90% respondents. Information about danger signs during pregnancy were received by 77.89% of the respondents.Conclusion : Utilization of Antenatal care service was higher in the study area. Most of the mothers had idea about benefit of ANC. Mother's education, family support, behaviour, availability of health care service provider and distance of health centre influence higher utilization. Therefore, to strengthen and intensify the ANC service at all level of health care delivery throughout the country is necessary for sustainability and targeting suboptimum ANC utilization group.Northern International Medical College Journal Vol.6(1) 2014: 25-28